Enhancing Curatorial Competencies : A New Media Art Curator Incubation Model in Indonesia - Jeon, Jeong Ok; Masunah, Juju; Soeteja, Zakarias S. (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to develop an incubation model to improve curator’s competencies on new media art curatorial practice. The incubation model contains a series of learning modules by which Indonesian young curators acquire theoretical knowledge and practical skills to develop and execute a new media art curatorial project. This research used a qualitative approach with a method of design-based research. The research process includes analysis, design, implementation, and evaluation. After analysing the mentees’ curatorial competencies, incubation model was designed based on four steps of curation: (1) Concept Development, (2) Artwork Selection, (3) Exhibition Design, and (4) Exhibition Communication. The research participants include 8 mentors, 9 mentees, and 3 facilitators for June mentorship, and 3 mentors, 2 curators, 4 artists, and 4 organizers for November exhibition. Data were collected through participatory observation, document studies, and personal reflection, which were interpreted through content analysis method. The result of the research is that implementing the four steps of curation in the new media art curator incubation model led to an improvement in 10 curatorial competencies for two mentees, and mostly 8 curatorial competencies for seven mentees. However, the limitation of this research is that ARCOLABS, the incubator, provided different levels of management to its mentees. Therefore, the research recommends that ARCOLABS should ensure fair treatment to all mentees to properly evaluate the improvement of curatorial competencies. For future research, the new media art curator incubation model should be redesigned and appropriately implemented to meet the required curatorial competencies.